2012
DOI: 10.1177/0486613412447059
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Tendency for the Rate of Profit to Fall? Econometric Evidence for the U.S. Economy, 1948-2007

Abstract: The law of the tendential fall in the rate of profit has been at the center of theoretical and empirical debates within Marxian political economy ever since the publication of Volume III of Capital. An important limitation of this literature is the absence of a comprehensive econometric analysis of the behaviour of the rate of profit. In this paper, we attempt to fill this lacuna in two ways. First, we investigate the time series properties of the profit rate series. The evidence suggests that the rate of prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 24 publications
0
11
0
4
Order By: Relevance
“…Although some scholars have argued in favor of the validity of the tendency of the profit rate to fall (Glyn and Sutcliffe, ; Rosdolsky, ; Shaikh, ; Glyn, ; Kliman, ), others have rejected the existence of such a tendency (Roemer, ; Bowles, ). Other scholars argue that there is no secular upwards or downwards trend in the profit rate resulting from capitalist development (Foley, ; Michl, ; Moseley, ; Duménil and Lévy, ; Foley and Michl, ; cited in Basu and Manolakos, ). Competition within the capitalist system forces firms to reduce their costs of production by increasing the degree of mechanization in production, leading to enhanced productivity of labor.…”
Section: Crisis Theory and The Effect Of Military Expenditures On Promentioning
confidence: 99%
“…Although some scholars have argued in favor of the validity of the tendency of the profit rate to fall (Glyn and Sutcliffe, ; Rosdolsky, ; Shaikh, ; Glyn, ; Kliman, ), others have rejected the existence of such a tendency (Roemer, ; Bowles, ). Other scholars argue that there is no secular upwards or downwards trend in the profit rate resulting from capitalist development (Foley, ; Michl, ; Moseley, ; Duménil and Lévy, ; Foley and Michl, ; cited in Basu and Manolakos, ). Competition within the capitalist system forces firms to reduce their costs of production by increasing the degree of mechanization in production, leading to enhanced productivity of labor.…”
Section: Crisis Theory and The Effect Of Military Expenditures On Promentioning
confidence: 99%
“…Basu and Manolakos () pointed out that there were two important shortcomings of this empirical literature. First, it did not take account of the time series properties of the rate of profit.…”
Section: Profitability Analysismentioning
confidence: 99%
“…Many researchers merely used exploratory data analysis, like visual inspection of time series plots or fitting trend lines to the profit rate series, to test the validity of the LTFRP. Basu and Manolakos (2013) pointed out that there were two important shortcomings of this empirical literature. First, it did not take account of the time series properties of the rate of profit.…”
Section: Econometric Analysis Of the Ltfrpmentioning
confidence: 99%
See 1 more Smart Citation
“…See Roberts (2009Roberts ( , 2011 for references to other research. Basu and Manolakos (2010) applied econometric analysis to the US economy between 1948 and 2007 and found that there was a secular tendency for the rate of profit to fall with a measurable decline of about 0.3 percent a year "after controlling for countertendencies." Roberts finds an average decline of 0.4 percent a year through 2009 using the latest data.…”
Section: Notesmentioning
confidence: 99%